Positive Self-Talk: Upaya untuk Meningkatkan Kepercayaan Diri pada Siswa SMP - Adiva Istighfarini; Nur Ainy Fardana Nawangsari (Universitas PGRI Kanjuruhan Malang, 2025)
Self-confidence is important for students to help the learning process run smoothly. The aim of this research is to test the effectiveness of positive self-talk techniques in increasing self-confidence in junior high school students. The subjects in the research were 5 students on grade 8 junior high school who had low category scores based on the Self-Confidence Assessment Instrument. This research uses a pre-experimental one group pretest-posttest method. The training procedure uses the training stages of the research. The results show that positive self-talk training is able to help students become more confident. The statistical results show a significance value of 0.043<0.05, which means there is a difference in knowledge between participants before and after the training. Thus, the Positive Self-Talk training program to increase students' self-confidence can be used as an intervention to help increase self-confidence in junior high school students.